2022
DOI: 10.1007/s11356-022-19702-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemical variables, antioxidative status, and histological features of intestinal, gill, and liver tissues of African catfish (Clarias gariepinus) exposed to high salinity and high-temperature stress

Abstract: African catfish is a freshwater species with a high ability to resist brackish water conditions, but heat stress may impair the health status of fish. Thus, the impact of varying levels of water salinity (0, 4, 8, and 12 ppt) was investigated on the growth performance, survival rate, and blood biochemistry of African catfish (average weight: 180.58 ± 2.8 g and average length: 38 ± 1.2 cm) for 4 weeks; then, fish were stressed with high temperature (32 °C) for 72 h. The growth performance and survival rate were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 63 publications
3
7
1
Order By: Relevance
“…Moreover, lower contents of antioxidant enzymes in tissues (liver, gills, and kidneys) of cat fish [ 74 ], reduced glutathione in the liver of Delta smelt [ 75 ], Jundiara fish [ 76 ], and lower values of reduced glutathione and superoxide dismutase in plasma of gold fish [ 77 ] due to various toxicants have been recorded. In contrast to our results, increased contents of superoxide dismutase, peroxidase, reduced glutathione, and catalase in different species of fish including Nile tilapia [ 78 ], Catla catla [ 68 ], Anoplopoma fimbria [ 27 ], and Clarias gariepinus [ 79 ] reared in water having higher salinity have been recorded.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, lower contents of antioxidant enzymes in tissues (liver, gills, and kidneys) of cat fish [ 74 ], reduced glutathione in the liver of Delta smelt [ 75 ], Jundiara fish [ 76 ], and lower values of reduced glutathione and superoxide dismutase in plasma of gold fish [ 77 ] due to various toxicants have been recorded. In contrast to our results, increased contents of superoxide dismutase, peroxidase, reduced glutathione, and catalase in different species of fish including Nile tilapia [ 78 ], Catla catla [ 68 ], Anoplopoma fimbria [ 27 ], and Clarias gariepinus [ 79 ] reared in water having higher salinity have been recorded.…”
Section: Discussioncontrasting
confidence: 99%
“…These results indicate that P. hypophthalmus can survive at water salinities up to 8.0‰. In our study, the decreased SR of P. hypophthalmus may be associated with decreased feed utilization and impaired overall health status of the exposed fish [45,46]. Similar to growth parameters, several inconsistent results were also found in the fish SR among the previously published papers.…”
Section: Discussionsupporting
confidence: 51%
“…In our study, we observed higher AST and ALT levels at 24 and 48 h, respectively, in response to 26‰ salinity compared to the 0‰ group. Similarly, higher-salinity treatment was found to increase blood AST and ALT levels in Clarias gariepinus [54]. Furthermore, AKP activity maintained a lower level in the 26‰ group than that in 0‰ group throughout the experimental period, which was similar to that in the Eriocheir sinensis [36].…”
Section: Discussionsupporting
confidence: 54%